2017
DOI: 10.1001/jamacardio.2017.3425
|View full text |Cite
|
Sign up to set email alerts
|

Association of Paravalvular Regurgitation With 1-Year Outcomes After Transcatheter Aortic Valve Replacement With the SAPIEN 3 Valve

Abstract: clinicaltrials.gov Identifier: NCT01314313.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(79 citation statements)
references
References 25 publications
(62 reference statements)
6
65
3
1
Order By: Relevance
“…This might be due to the low AR rates, with mostly none/trace or mild AR severity. However, this lack of association between mild AR and clinical outcomes is in accordance with the FRANCE-2 Registry and the PART-NER II SAPIEN 3 trial [25,26].…”
Section: Discussionsupporting
confidence: 70%
“…This might be due to the low AR rates, with mostly none/trace or mild AR severity. However, this lack of association between mild AR and clinical outcomes is in accordance with the FRANCE-2 Registry and the PART-NER II SAPIEN 3 trial [25,26].…”
Section: Discussionsupporting
confidence: 70%
“…Patients undergoing new pacemaker implantation following TAVR have a 30-day heart failure readmission rate of 22.4% compared with 16.1% for patients without a new pacemaker 13. For patients enrolled in the Placement of AoRTic TraNscathetER Valves (PARTNER II) trial, TAVR patients with moderate or greater paravalvular aortic regurgitation had an HR of 2.27 (95% CI 1.31 to 3.94) for 1-year readmission compared with patients with mild or no paravalvular regurgitation 25. A single study confirmed the relationship between moderate or greater pre-TAVR TR and 30-day readmission 26.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with at least moderate PVR had higher 1‐year mortality (HR, 2.40; P = 0.005) and the composite of mortality/re‐hospitalization (HR, 2.35; P < 0 .001). Patients with moderate PVR at 30 days had a decrease in PVR severity at 1 year …”
Section: Complicationsmentioning
confidence: 96%